Comparative effects of lidocaine and esmolol in attenuating the hemodynamic response to laryngoscopy and intubation - Koju, Ram Bhakta; Dongol, Y (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Transient hemodynamic instability is an inevitable outcome of laryngoscopy and intubation which can have serious effects in patients with COPD, heart disease and hypertension. Hemodynamic stability is one of the main goals of the anesthesiologist. This study was performed to compare the safety and effectiveness of lidocaine and esmolol in comparison to placebo-control group, in modifying the hemodynamic response to laryngoscopy and intubation. Methods: After approval of the study protocol by the institutional review board (IRB), written informed consent was obtained from each patient. It was a randomized placebo-controlled, double-blinded study. 75 patients of American Society of Anesthesiologists physical status I and II, scheduled for general surgery under GA, aged between 20-60 years were randomly allocated into three groups: placebo control group (n=25), lidocaine group (n=25) and esmolol group (n=25). Placebo group received 12 ml normal saline, lidocaine group received 1.5mg/kg lidocaine (total volume 12 ml) and esmolol group received 1.4mg/kg esmolol (total volume 12ml). Results: Following laryngoscopy and intubation, the increase in systolic blood pressure, diastolic blood pressure and heart rate were significantly lower (p < 0.05) in esmolol group compared to the lidocaine and placebo group but there was no statistical significance (p > 0.05) between control and lidocaine group. Conclusion: Esmolol 1.4 mg/kg IV was significantly more effective in controlling the hemodynamic response following laryngoscopy and intubation in comparison to lidocaine 1.5 mg/kg. Journal of Society of Surgeons of Nepal Vol. 17, No. 2, 2014, Page: 23-30